Is the Stationary Wave Bias in CMIP5 Simulations Driven by Latent Heating Biases?. Issue 4 (22nd February 2021) - Park, Mingyu; Lee, Sukyoung
Abstract: Atmospheric stationary waves play an important role in regional climate. In phase 5 of the Coupled Model Intercomparison Project (CMIP5), a prior study found that there are systematic biases in Arctic moisture intrusions caused by stationary eddy meridional wind biases. In this study, using initial‐value model calculations, it is shown that CMIP5 latent heating biases in the tropics and midlatitudes play a substantial role in generating the systematic meridional wind bias poleward of 50°N. It is further shown that the midlatitude heating biases are in part driven by the circulation caused by the tropical and subtropical heating biases. These results indicate that the systematic stationary meridional wind biases poleward of 50°N can be traced to systematic model biases in tropical and extratropical latent heating. Therefore, reliable regional climate projections likely hinge on accurate representations of moist processes upstream of the region of interest and in the tropics. Plain Language Summary: Stationary waves are time‐mean, zonally asymmetric features of the atmospheric circulation that affects regional climate variability. The Coupled Model Intercomparison Project Phase 5 (CMIP5) models have been widely used to predict regional climate changes. However, because of uncertainties in circulation changes, large uncertainties remain in the predicted regional temperature and precipitation. Thus, it is critical that climatological stationary waves are accurately represented in climate models. It is shown here that CMIP5 models have systematic biases in stationary eddy meridional wind poleward of 50°N during winter. To investigate a possible source of these biases, idealized model experiments are performed. Results show that tropical and extratropical latent heating biases in CMIP5 models can generate wind fields that resemble the wind bias. These findings underscore that in order to improve model performance in predicting regional climate changes, it is important to accurately model moist processes, not only over the region of interest, but also upstream and even in the tropics. Key Points: Climate models have systematic eddy meridional wind biases poleward of 50°N during boreal winter Regional precipitation biases generate eddy meridional wind anomalies that resemble the bias pattern in climate models Extratropical precipitation biases are caused in part by circulations driven by tropical and subtropical precipitation biases